2006
DOI: 10.1152/ajpheart.00930.2005
|View full text |Cite
|
Sign up to set email alerts
|

Thromboxane A2-induced arrhythmias in the anesthetized rabbit

Abstract: Experiments were conducted in the anesthetized rabbit to investigate mechanisms for arrhythmias that occur after left atrial injection of the thromboxane A(2) (TxA(2)) mimetic U-46619. Arrhythmias were primarily of ventricular origin, dose dependent in frequency, and TxA(2) receptor mediated. The response was receptor specific since arrhythmias were absent after pretreatment with a specific TxA(2) receptor antagonist (SQ-29548) and did not occur in response to another prostaglandin, PGF(2alpha). Alterations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 48 publications
4
20
0
Order By: Relevance
“…During the course of these in vivo experiments in the anesthetized adult rabbit, it was noted that left atrial injec-tions of U46619 also induced arrhythmias. These U46619-induced arrhythmias were documented in a subsequent study and found to be ventricular in origin and were inhibited by pretreatment with SQ29548, a specific inhibitor of the TXA 2 receptor (TXA 2 R also known as TP) (Wacker et al, 2006). Coronary blood flow was measured during these experiments and was not significantly altered by the injections of U46619, and there were no ST segment changes in the ECG recordings.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…During the course of these in vivo experiments in the anesthetized adult rabbit, it was noted that left atrial injec-tions of U46619 also induced arrhythmias. These U46619-induced arrhythmias were documented in a subsequent study and found to be ventricular in origin and were inhibited by pretreatment with SQ29548, a specific inhibitor of the TXA 2 receptor (TXA 2 R also known as TP) (Wacker et al, 2006). Coronary blood flow was measured during these experiments and was not significantly altered by the injections of U46619, and there were no ST segment changes in the ECG recordings.…”
mentioning
confidence: 80%
“…Rabbits were prepared and anesthetized as described in our previous studies (Wacker et al, 2002(Wacker et al, , 2003(Wacker et al, , 2006. Arterial blood pressure was measured via a right femoral artery catheter connected to a pressure transducer and analyzed with PowerLab software (ADInstruments; Colorado Springs, CO).…”
Section: Rt-pcrmentioning
confidence: 99%
See 3 more Smart Citations